Mothers with mental disorders and their children: risk and development: DOI: 10.15343/0104-7809.201017381 - Maria Fernanda Barboza Cid; Thelma Simões Matsukura (O Mundo da Saúde)
Considering that the literature points to mental disorders in mothers as an important risk factor regarding children mental health, the objective of the present study was to identify and to compare parental styles and levels of social support of mothers with mental disorders with sane mothers as well as the levels of emotional development of their children. Subjects were 5 mothers with mental disorders and their children and 5 sane mothers and their children. The instruments used for data collection were a Questionnaire of Capacities and Difficulties, an Inventory of Parental Style and the Questionnaire of Social Support. Results indicated that mothers with mental disorders are less satisfied with the social support they receive, and have a Risk Parental Style as regards the development of antisocial behaviors in their children.